The effect of brief self-management intervention for hemodialysis patients (HED-SMART) on trajectories of depressive and anxious symptoms - Griva, Konstadina (2020)
Objective: Depression is often comorbid with End-Stage Renal Disease, and associated with poor adherence and clinical outcomes but course of symptoms is variable. This study sought to describe the long-term trajectories of anxiety and depression in hemodialysis patients, to identify predictors of these trajectories over 12 months and to evaluate the effectiveness of the HEmoDialysis Self-Management Randomized Trial (HED SMART) against usual care on symptoms of anxiety and depression. Methods: A secondary analysis of data from a randomized controlled trial that contrasted HED SMART (n = 101) against usual care (n = 134). Depressive and anxious symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS) at baseline, 1 week and at 3 and 9 months post-intervention. Latent class growth analysis identified trajectories of depression and anxiety, and their sociodemographic and clinical predictors. Results: Symptoms of depression and anxiety over 12 months were characterized by two trajectories: low stable (depression: 55%; anxiety: 59%) with non-clinical levels of distress, and high stable (depression: 45%; anxiety: 41%) with clinical levels of distress. HED SMART predicted significant reductions in depression relative to usual care. A similar trend was noted for anxiety. Younger age, Chinese ethnicity, and more comorbidities were associated with persistent high depression. Younger age and shorter dialysis vintage was associated with persistent high anxiety. Conclusion: A brief self-management intervention designed to support behavioral change can also lead to significant reductions in symptoms of depression and may be of great value for younger HD patients shown to be at greater risk for persistent distress.